Strengthening the evidence base for graduate communication skills : final report. - Arkoudis, Sophie; Harris, Anne; Guillemin, Marilys; Nayor, Ryan; Kelly, Paula; Oliver, Ron; Hunter, Kerry; Griffiths, Neela; McKenzie, Jo; Lynch, Andrea (Office for Learning and Teaching, 2018)
Final report from a project that focused on university graduates' communication skills. The project team created the Distributed Expertise Model, which aims to assist universities in developing, assessing and demonstrating graduates' communication skills. The model, based on a whole-of-program approach, utilises current expertise already available in universities and identifies high impact practices for student learning. Research explored these questions: How do deputy vice-chancellors (academic and/or learning and teaching) and program leaders know that their graduates have attained threshold oral and written communication skills? Within programs, what takes place as part of the curriculum design to assure communication skills are developed and assessed across a student's course? What are the practices that have high impact? How is the impact on student learning evaluated? How scalable are the practices? How can institutions demonstrate to external stakeholders that their graduates have achieved the communication skills for further study or employment?